2012
DOI: 10.1260/2040-2295.3.4.503
|View full text |Cite
|
Sign up to set email alerts
|

Protein Analytical Assays for Diagnosing, Monitoring, and Choosing Treatment for Cancer Patients

Abstract: Cancer treatment is often hindered by inadequate methods for diagnosing the disease or insufficient predictive capacity regarding therapeutic efficacy. Targeted cancer treatments, including Bcr-Abl and EGFR kinase inhibitors, have increased survival for some cancer patients but are ineffective in other patients. In addition, many patients who initially respond to targeted inhibitor therapy develop resistance during the course of treatment. Molecular analysis of cancer cells has emerged as a means to tailor tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(24 citation statements)
references
References 128 publications
(266 reference statements)
0
24
0
Order By: Relevance
“…For precision medicine, PTM signatures may either be identified in disease models and then validated in clinical samples or directly identified using clinical samples. Although, for example, specific changes in phosphorylation and glycosylation are increasingly reported as potential markers of disease, and many PTM assays have been developed so far (for instance reviewed in [23][24][25]), only few are really routinely used for diagnostic purposes to date, due to a variety of reasons [26]. We are still in the early days of PTM-specific research and detection and many potential PTM biomarkers and the corresponding assays still need to be validated extensively.…”
Section: Can Ptms Be Used As Biomarkers?mentioning
confidence: 99%
“…For precision medicine, PTM signatures may either be identified in disease models and then validated in clinical samples or directly identified using clinical samples. Although, for example, specific changes in phosphorylation and glycosylation are increasingly reported as potential markers of disease, and many PTM assays have been developed so far (for instance reviewed in [23][24][25]), only few are really routinely used for diagnostic purposes to date, due to a variety of reasons [26]. We are still in the early days of PTM-specific research and detection and many potential PTM biomarkers and the corresponding assays still need to be validated extensively.…”
Section: Can Ptms Be Used As Biomarkers?mentioning
confidence: 99%
“…12 Additionally, sample fixation has the potential to induce artificial patterns particularly for signalling PTMs such as protein phosphorylation, or, conversely, may fail to preserve these. In IHC, results are often interpreted in a semi-quantitative manner, and are manually ranked based on staining intensity which introduces subjectivity and variability into the assays, 13 with a continuing need for improved standardization. 14,15 Recently, Morales-Betanzos et al demonstrated that IHC methods for detecting programmed death-ligand 1 (PD-L1), an important companion diagnostics for immune checkpoint therapies, can suffer severely from interference by endogenous PD-L1 glycosylation patterns that prevent proper epitope recognition, leading to underestimation of PD-L1 expression levels.…”
Section: The Demand For Clinical Diagnostic Assaysmentioning
confidence: 99%
“…Development of analytical methods for biomarkers such as proteins and peptides has great significance in the fields of clinical diagnostics, environmental monitoring, food safety tests, and proteomics . Immunoassays, which are those of the most common methods for protein analyses, can sensitively detect desired analytes, because proteins are recognized through antigen–antibody interactions in measurement systems.…”
Section: Figurementioning
confidence: 99%